2003
DOI: 10.1002/ajmg.a.20026
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of a patient with central nervous system dysmyelination and cryptic unbalanced translocation between chromosomes 4q and 18q

Abstract: We report on a 12-year-old boy who presented with delayed development and CNS dysmyelination. Genetic studies showed a normal 46,XY karyotype by routine cytogenetic analysis, and 46,XY.ish del(18)(q23)(D18Z1+, MBP-) by FISH using a locus-specific probe for the MBP gene (18q23). Though the patient appeared to have normal chromosome 18s by repeated high resolution banding analysis, his clinical features were suggestive of a deletion of 18q. These included hearing loss secondary to stenosis of the external audito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
30
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 17 publications
5
30
0
Order By: Relevance
“…The 3-kb LTR is an HERV-H transposable element. This element has been implicated in the formation of a de novo der(18)t(4;18)(q35.1;q22.3), complementary to the der(4)t(4;18)(q35.1;q22.3) identified here (Gunn et al 2003;Moncla et al 2004;Horbinski et al 2008;Hermetz et al 2012). In addition, in case 7, the breakpoint junction could not be sequenced, but the breakpoint region on both chromosomes harbors an intact 6-kb L1PA4 element, suggesting that NAHR occurred within.…”
Section: Resultsmentioning
confidence: 92%
“…The 3-kb LTR is an HERV-H transposable element. This element has been implicated in the formation of a de novo der(18)t(4;18)(q35.1;q22.3), complementary to the der(4)t(4;18)(q35.1;q22.3) identified here (Gunn et al 2003;Moncla et al 2004;Horbinski et al 2008;Hermetz et al 2012). In addition, in case 7, the breakpoint junction could not be sequenced, but the breakpoint region on both chromosomes harbors an intact 6-kb L1PA4 element, suggesting that NAHR occurred within.…”
Section: Resultsmentioning
confidence: 92%
“…Using this technology, cases of unexplained MR can be investigated molecularly by performing a genome-wide scan of DNA imbalance [see Albertson and Pinkel, 2003 for review]. Gunn et al [2003] have recently demonstrated the use of array-CGH to reveal both cryptic gain and loss in a patient with a normal G-banded karyotype but with features suggestive of a chromosome abnormality. Therefore, to investigate the possibility of submicroscopic deletions or duplications at the breakpoints of the complex rearrangement in our patient, we used array-CGH to screen the whole genome of this patient at a resolution of 3 Mb.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have already emphasized the value of this approach. [31][32][33][34] The versatility of high-density oligonucleotide arrays is a function of in situ probe synthesis chemistry, the digital workflow that controls that synthesis, and creative feature and array formats. Users can generate customized arrays quickly for two possible clinical uses.…”
Section: Clinical Contexts For Whole-genome Arraysmentioning
confidence: 99%